A value perspective of service interaction quality: The case of immigrants returning to native countries as medical tourists - Pham Ngoc Thuy; Le Nguyen Hau; Nguyen Kim Ngoc Duyen (International Journal of Quality Innovation, 2019)
Marketing literature shows that the interaction between service encounters and customers is essential for the value creation process. However, little is known about how interaction contributes to customer value in the special context of immigrants living in more-developed countries, who return to their native countries for medical service. Based on the data collected from overseas Vietnamese, this study investigates the effects of interaction quality on different forms of service value, leading to positive word-of-mouth. The findings indicate that interaction quality strongly affects customer perception of quality value and social value and moderately affects price value. In turn, these three forms of value significantly affect positive word-of-mouth. By linking perceived quality, social and price value with word-of-mouth, the present study suggests an effective way to promote this special form of medical service to immigrants living outside the country.
Keywords: 650; Medical tourism; Dental service; Interaction quality; Customer value; Vietnam